Business Economics - N. Gregory Mankiw; Mark P. Taylor; Andrew Ashwin (UK Cengage, 2019)
Business Economics brings together three authors with extensive experience in teaching both business and economics students. The text provides a clear and easy-to-read guide to the practical uses of economics in a business environment. Recent examples and cases throughout the text demonstrate the key economic issues facing the business world. Now covering the global economy, Brexit, the gig economy and international trade theories, the third edition ensures that students are up to date with the latest developments in business economics.
Keywords: Economics; Business; Textbooks; The International Market Environment (ECO1021-N)